'A City upon a Hill': The Wire and Its Distillation of the United States Polity. (21st January 2014) - Wheeler, Mark
<x xml:space="preserve">Abstract</x> The Home Box Office's series The Wire (2002–2008) provides an informed critique of the decline of the democratic American ideal of the 'city upon a hill'. From its inception as a police procedural, it expanded its interests across the dystopian city of Baltimore to consider the linkage between drug crimes, policing, the collapse of blue‐collar life, social deprivation, institutional compromise, the public school system, media compliance and political self‐interest. Therefore, this article will situate The Wire into the debates that have defined the US polity and will discuss how it employs the narrative conventions of a contemporary thriller to offer an alternative view of American democracy.